PENGANTAR HUKUM PERBANKAN SYARIAH: PERKEMBANGAN, TANTANGAN, DAN PROSPEKNYA DI ERA DIGITAL - m.ilham; HAYATI, NUR (Jurnal Ilmiah Ekonomi Islam, 2025)
This study aims to analyze the development, challenges, and prospects of Islamic banking law in the digital era with a focus on legal certainty, data security, and Islamic digital literacy. This study uses a qualitative design with a case study approach on Islamic banks in Indonesia. The research setting was conducted in Jakarta as the center of Islamic banking regulation and practice. The research population included Islamic banking practitioners, regulators, and customers, while the sample was selected purposively. Data were obtained through in-depth interviews, document studies, and observations. The results show that Islamic banking regulations have undergone positive developments through the support of the OJK and DSN-MUI for the digitization of services. However, there are still major challenges in the form of unclear regulations on digital contracts, high cybercrime risks with an average of 120 attacks per month, and low Islamic digital literacy. On the other hand, the prospects for digital Islamic banking are very promising, supported by more than 196 million internet users in Indonesia. Thus, the success of the transformation of Islamic banking law in the digital era is highly dependent on the synergy of regulations, literacy, and the strengthening of security infrastructure.